Bridging the gap: returning genetic results to indigenous communities in Latin America - Arango-Isaza, Epifanía; Aninao, María José; Campbell, Roberto; Martínez, Felipe I.; Shimizu, Kentaro K.; Barbieri, Chiara (Frontiers in Genetics, 2023)
In response to inequality in access to genomics research, efforts are underway to include underrepresented minorities, but explicit (and enforcing) guidelines are mostly targeted toward the Global North. In this work, we elaborate on the need to return scientific results to indigenous communities, reporting the actions we have taken in a recent genomic study with Mapuche communities in Chile. Our approach acknowledged the social dynamics perpetuating colonial hierarchies. We framed genetic results to empower indigenous knowledge and communities' history and identities. A fundamental step in our strategy has been sharing the results with the communities before publishing the scientific paper, which allowed us to incorporate community perspectives. We faced the challenge of translating genetic concepts like admixture, emphasizing the distinction between identity and biology. To reach a broad and diverse audience, we disseminated the study results to single community members, cultural representatives, and high schools, highlighting the importance of the history of the region before the European contact. To facilitate results dissemination, we prepared didactic material and a report in Spanish written in non-specialized language, targeting a wider Latin American readership. This work illustrates the benefits of discussing scientific findings with indigenous communities, demonstrating that a collaborative and culturally sensitive approach fosters knowledge sharing and community empowerment and challenges power dynamics in genetic research. Bridging the gap between academia and indigenous communities promotes equity and inclusion in scientific endeavors.